Employment effects of a statutory minimum wage : evidence from a national reform of the German apprenticeship market - Dörsam, Michael [Verfasser]; Langen, Henrika [Verfasser] (My University, 2025)
„To enhance the attractiveness of vocational education and training and to secure an adequate supply of skilled labour, the German government introduced a statutory minimum apprenticeship wage. Since January 1, 2020, apprentices who start their training have been entitled to a minimum wage that increases annually. Using administrative register data on apprenticeship contracts, we estimate the causal effect of this legislation on apprentice employment. Exploiting regional and occupational variation in the share of apprenticeships paid at the minimum wage, we apply standard difference-indifferences, triple-difference, and synthetic difference-in-differences models. Our results indicate that the minimum apprenticeship wage increased the number of apprenticeship contracts while reducing the contract termination rate in low-wage occupations. We also find considerable heterogeneity across occupations, which may be best explained by differences in exposure to skilled labour shortages and changes in apprentices’ educational attainment.“ (authors‘ abstract; BIBB-Doku)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; S 2.1.6 Arbeits- & Tarifrecht; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; 370; Ausbildungsstellenmarkt; Ausbildungsvergütung; Mindestlohn; Beschäftigungseffekte; Berufsausbildung; Attraktivität; Berufsbereiche; Regionale Faktoren